Analyzing Tanker Ship Berthing Delays at Pertamina Refinery Unit II Dumai Terminal - Octi Avriani; Mardiana Mardiana; Sukardi Sukardi (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This research investigates the causes and mitigation strategies for tanker ship berthing delays at the PERTAMINA Refinery Unit II Dumai special terminal. The study identifies key issues including dock capacity limitations, adverse weather conditions, insufficient land tank storage, and restrictions on night-time berthing. Data were collected through qualitative research and descriptive analysis involving observations, interviews, and documentation from August 2023 to August 2024. Findings reveal that limited dock capacity and adverse weather significantly contribute to delays, while storage limitations and night-time restrictions further exacerbate the problem. The research highlights the need for dock capacity expansion, improved weather forecasting, enhanced storage management, and safe night-time operational practices. Recommendations include infrastructure upgrades, advanced technological investments, and flexible operational strategies to address these challenges. The study provides valuable insights for improving terminal efficiency and offers a foundation for future research and practical applications in maritime logistics